Evaluation Of Parameters Governing The Release Rate Of Phosphate Ions From Chitosan-Coated Phosphorus Fertilizer Pellets - Ahmad, Nor Naimah Rosyadah (2013)
Coated fertilizers, which belong to the group of controlled-release fertilizer (CRF) have been widely used in agricultural field in order to reduce the ground water pollution and at the same time increase the nutrient use efficiency by crops. Chitosan is one of promising biopolymers that can be used as a coating material in order to control the release rate of nutrients from fertilizer pellets due to its excellent properties. Most of the previous studies based on the chitosan coating were focused on the urea and compound fertilizers of nitrogen-phosphorus-potassium (NPK). Studies regarding the chitosan-coated phosphorus fertilizers have not been addressed so far. Furthermore, previous studies also neglected the evaluation of parameters that govern the nutrient release rate using the mechanistic model. Understanding the transport parameters such as diffusion coefficient of nutrient through coated pellet is very important in order to improve the design of fertilizers. This study is mainly focused on investigating the release rate of phosphate ions from the chitosan-coated phosphorus fertilizer pellets and evaluation of parameters that controlled the nutrient release using mechanistic model. Appropriate experiments were carried out in order to determine the phosphate ions release rate from pellets with different number of chitosan coating layers (one, two and three layers) under variation of pH conditions (pH 5.7, 7.1 and 8.5). Experiments were also conducted for short and long period of release tests.